Examining the influence of Mother-in-law on family planning use in South Asia: insights from Bangladesh, India, Nepal, and Pakistan - Manas Ranjan Pradhan; Sourav Mondal (BMC, 2023)
Abstract Background Contraceptive use contributes to improved maternal and child health, education, empowerment of women, slow population growth, and economic development. The role of the family in influencing women's health and health-seeking behavior is undergoing significant changes, owing to higher education, media exposure, and numerous government initiatives, in addition to women's enhanced agency across South Asia. Against this backdrop, this study assesses the relationship between women's living arrangements and contraceptive methods used in selected south Asian countries (India, Pakistan, Nepal, and Bangladesh). Methods Data of currently married women aged 15-49 from the recent round of Demographic and Health Survey (DHS) of four South Asian countries, i.e., Nepal (2016), Pakistan (2017-18), Bangladesh (2017-18), and India (2019-21) had been used. Bivariate and multinomial logistic regression was performed using Stata with a 5% significance level. Results Living arrangement of women had a significant association with contraceptive use in South Asia. The Mother-in-law (MIL) influenced the contraceptive method used by the Daughter-in-law (DIL), albeit a country-specific method choice. Modern limiting methods were significantly higher among women living with MIL in India. The use of the modern spacing method was considerably high among women co-residing with husband and/or unmarried child(ren) and MIL in Nepal and India. In Bangladesh, women living with husband and other family member including MIL were more likely to use modern spacing methods.. Women co-residing with the MIL had a higher likelihood of using any traditional contraceptive method in India. Conclusions The study suggests family planning program to cover MIL for enhancing their understanding on the benefits of contraceptive use and modifying norms around fertility. Strengthening the interaction between the grassroots level health workers and the MIL, enhancing social network of DIL may help informed choice and enhance the use of modern spacing methods. Women's family planning demands met with modern contraception, and informed contraceptive choices, must also be achieved to reach the 2030 Agenda for Sustainable Development.